Shopping Motivation as a Moderator in the Retail Service Evaluation - Luk, S.T.; Sharma, Piyush; Chen, I.S. (Emerald Group Publishing Limited, 2013)
Purpose – Prior research explores the moderating effects of age and gender on the relationships in the comprehensive service evaluation model, but it ignores the role of contextual variables. The study aims to test the moderating effect of an important contextual variable (shopping motivation) on the service evaluation process. Design/methodology/approach – Responses were collected from 2,727 shoppers in six retail categories (cosmetics, electronics, fashion, jewelry, telecommunication services, and department stores) using a mall-intercept approach and all the hypotheses were tested using structural equation modeling technique. Findings – The study finds that relationships among sacrifice, value, satisfaction, and behavioral intentions are stronger in retail categories with utilitarian vs hedonic shopping motivation. In contrast, the relationships among service quality, value, satisfaction, and behavioral intentions are stronger in hedonic vs utilitarian retail categories. Research limitations/implications – This paper uses a cross-sectional survey to test all the hypotheses, hence it cannot study actual shopping behavior in future. Moreover, it examines shopping motivation at a retail category level and not at individual shopper level. The results may also vary based on cross-cultural differences in customer expectations and perceptions.Practical implications – The findings would help retail managers to identify relevant service dimensions, to improve perceived service quality, customer satisfaction, and value for the shoppers in their stores, which in turn may lead to more favorable behavioral intentions. Originality/value – This paper offers new insights on the differences in expectations, perceptions, and evaluations of shoppers in hedonic vs utilitarian retail categories, and introduces the moderating role of shopping motivation, an important contextual variable.